(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This article analyzes the field of political linguistics, which is one of the branches of modern linguistics, as well as the concepts of political speech and political discourse in linguistics, and studies the ideas expressed in English and world linguistics.